Radiofrequency-assisted liver resection: higher incidence of infectious complications? - Subrt, Z; Ferko, A; Jon, B; Cecka, F (Acta chirurgica Belgica, 2011)
AIM: To evaluate clinical experience with radiofrequency (RF)-assisted liver resection in non-cirrhotic and non-cholestatic patients with metastatic liver disease. METHODS: A group of consecutive patients who underwent RF-assisted liver resection for metastatic liver disease was prospectively followed. RESULTS: Between July 2005 and April 2008, 95 liver RF-assisted liver resections were performed, 71 of them for metastatic liver disease. The mean hospital stay was 14 (range 5-40) days. The mean operation time was 141 (range 64-233) minutes. The mean duration of RF coagulation was 10 (range 9-12) minutes. A total of 37 complications in 24 (33%) patients were recorded, including 12 (16.9%) infected collections in resection line that had to be drained percutaneously. The 30-day postoperative mortality was zero. CONCLUSION: This study indicates that RF-assisted resection may have a benefit in decreasing peroperative blood loss and the number of blood transfusions. Nevertheless, an increased incidence of infectious complications and pleural effusions that required evacuation was noted.
Keywords: senioři; metastázy nádorů; Liver Neoplasms; senioři nad 80 let; nádory jater; Incidence; Česká republika; katetrizační ablace; Middle Aged; mužské pohlaví; hepatektomie; incidence; Prospective Studies; Adult; Czech Republic; Hepatectomy; Follow-Up Studies; Surgical Wound Infection; následné studie; Aged, 80 and over; Catheter Ablation; Neoplasm Metastasis; ženské pohlaví; Humans; prospektivní studie; lidé středního věku; rizikové faktory; dospělí; Female; Aged; Risk Factors; infekce chirurgické rány; lidé; Male